1990
DOI: 10.1210/endo-126-3-1599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1,25-Dihydroxyvitamin D3 on Induction of Chondrocyte Maturation in Culture: Extracellular Matrix Gene Expression and Morphology*

Abstract: Chondrocytes, derived from a tissue that remains as permanent hyaline cartilage in vivo (embryonic chicken caudal sterna) were treated with 10(-8) to 10(-8) M 1,25-dihydroxyvitamin D3 [1,25(OH)2D3]. These nonadherent rounded chondrocytes acquired an adherent, polygonal morphology in a dose-dependent fashion with 1,25(OH)2D3 treatment. During the first 4 days of 1,25(OH)2D3 treatment cell flattening was associated with a 10-fold increase in beta-actin and fibronectin and their corresponding messenger RNAs (mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 35 publications
1
26
0
2
Order By: Relevance
“…This implies a contribution of signals from the extracellular matrix that promotes the developmental sequence of osteoblast differentiation and a higher level of gene expression than in the absence of the extracellular matrix. The dependency on ascorbic acid and collagen matrix formation for expression of differentiation-related genes has also been observed for chondrocyte culture systems (Leboy et al, 1989;Gerstenfeld et al, 1990;Franceschi and Young, 1990).…”
Section: B Formation Of the Bone-like Extracellular Matrix In Vitro mentioning
confidence: 72%
“…This implies a contribution of signals from the extracellular matrix that promotes the developmental sequence of osteoblast differentiation and a higher level of gene expression than in the absence of the extracellular matrix. The dependency on ascorbic acid and collagen matrix formation for expression of differentiation-related genes has also been observed for chondrocyte culture systems (Leboy et al, 1989;Gerstenfeld et al, 1990;Franceschi and Young, 1990).…”
Section: B Formation Of the Bone-like Extracellular Matrix In Vitro mentioning
confidence: 72%
“…These findings show the lack of effect of l,25(OH)2D3 on cell attachment to the matrix because it has no effect on the expression of laminin receptor. l,25(OH)2D3-induced changes in the ex pression of extracellular matrix proteins have been reported in several normal tissue cells and tumor cells [19][20][21][22][23], Brackman [23] re ported that l,25(OH)2D3 induced a marked reduction in laminin and fibronectin expres sion using immunocytochemistry on murine fibroblast spheroids. Our own data shown in figure4 demonstrate that l,25(OH)2D3 in duces a reduction of the expression of laminin mRNA in a dose-dependent manner in HT1080 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of tumor cells with the extracellu lar matrix has an important role in tumor invasion and metastasis. It has been suggested that extracellular matrix proteins such as lam inin and fibronectin might signal through a protease system, leading to increased matrix synthesis [15,16], We have previously found that type IV collagenolytic and migration ac tivity of tumor cells were accelerated by cell attachment to laminin via the cell surface laminin receptor, suggesting that laminin plays an important role in the matrix degrada tion by tumor cells and cell migration [17,18], Recently, l,25(OH)2D3 has been reported to modulate the expression of extracellular ma trix proteins in several cell lines [19][20][21][22][23]. Brackman [23] reported that the hormone induced a substantial reduction in the expres sion of laminin and fibronectin from murine fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that 1,25(OH) 2 D 3 promotes chondrocytes differentiation of chondrocytes along the endochondral differentiation cascade (Gerstenfeld et al 1990). Prominent areas of chondrocytes were observed in the periosteum of ribs of Sm-treated rabbits, just beneath its outer layer (*).…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%